Neuroanatomically informed psychotherapy after mild brain injury: a single-case report of clinical improvement - Bordón Guerra, Rosario; Peñate Castro, Wenceslao; Ferreiro Díaz-Vélis, Eilin; Sosa Pérez, Coralia; Hernández Fleta, José Luis; Morera Molina, Jesús (Frontiers in Human Neuroscience, 2026)
Psychotherapeutic interventions following acquired brain injury often underestimate the influence of neural connectivity on emotional and cognitive recovery, contributing to treatment response variability. We present a single-case report of an adult with mild acquired brain injury, in whom diffusion tensor imaging (tractography) and neuropsychological assessment were integrated to guide individualized clinical planning. Baseline tractography revealed globally preserved white-matter organization with rightward asymmetries in the uncinate and superior longitudinal fasciculi–pathways involved in cognitive–emotional integration. This specific neuroanatomical profile informed a psychotherapeutic plan that prioritized attentional and experiential strategies, being functionally compatible with the preserved networks, over those requiring complex verbal-analytic processing. After 1 year of intervention (approximately 40 sessions), reassessment documented significant functional improvements, quantified by a reduction in anxiety to a non-clinical range (HADS-A: 11 → 6) and a normalization in cognitive flexibility (TMT-B: 190 → 128 s), without observable structural change. These findings validate the hypothesis that therapeutic change may arise from functional optimization within preserved networks rather than anatomical reorganization. This report proposes the functional compatibility framework as a transferable and theoretically grounded model for precision psychotherapy, bridging the gap between neuroscience and clinical practice.